Performance Evaluation of Bambusa Tulda Treated with Different Fire Retardant Compositions - Samani, Ajmal; Tripathi, Sadhna; Lal, Ram (Indian Forester, 2009)
The present paper deals with the treatment of Bambusa tulda with ten different fire retardant-cum-preservative compositions to offer protection against fire. The performance of treated bamboo against fire was tested for flame penetration, inflammability and rate of burning test as per Indian standards. Bambusa tulda treated with only four compositions passed all fire retardant tests.